1996
DOI: 10.1111/j.1476-5381.1996.tb15242.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation by eosinophils of gelatinase activity in the airway mucosa: comparative effects as a putative mediator of epithelial injury

Abstract: We have studied the release of gelatin‐degrading enzymes from isolated sheets of bronchial mucosa in the presence and absence of eosinophils. Isolated sheets of bovine bronchial mucosa released gelatin‐degrading activity in similar amounts from both the apical and basolateral aspects of the tissue. Gelatinolytic activity could not be increased by treatment of the mucosal sheets with calcium ionophore, A23187. The activity of the released gelatinases could be inhibited by chelation of divalent cations or by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…If the effect of the HDM proteinases were to activate epithelial cells to produce a metalloproteinase capable of cleaving Fas ligand then the inhibitory effect of BB‐250 could be simply explained. It is known that epithelial cells derived from lung can produce the matrix metalloproteinases gelatinase A and gelatinase B (Herbert et al , 1996; Robinson et al , 1997a; Canete‐Soler et al , 1994; Yao et al , 1996) but it is not known whether these enzymes cleave Fas ligand in this situation. A second possibility is that metalloproteinases are embedded in the Matrigel undercoats on which the epithelial cells are cultured and that these become activated by the HDM proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…If the effect of the HDM proteinases were to activate epithelial cells to produce a metalloproteinase capable of cleaving Fas ligand then the inhibitory effect of BB‐250 could be simply explained. It is known that epithelial cells derived from lung can produce the matrix metalloproteinases gelatinase A and gelatinase B (Herbert et al , 1996; Robinson et al , 1997a; Canete‐Soler et al , 1994; Yao et al , 1996) but it is not known whether these enzymes cleave Fas ligand in this situation. A second possibility is that metalloproteinases are embedded in the Matrigel undercoats on which the epithelial cells are cultured and that these become activated by the HDM proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…Additional sources of MMPs in the lung may be inflammatory cells that migrate into the lung during an inflammatory response (12). To date, a comprehensive examination of MMPs produced by lung-derived cells has not been performed in the normal human lung or in pathological conditions associated with lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that allergic sensitization might be facilitated by peptidase allergens that lead to cleavage of the extracellular domains of TJs [12,13]. It has also been speculated that activated eosinophils cause the bronchial epithelium to become hyperfragile by promoting cleavage of both lateral and basal adhesions of epithelial cells [14,15].…”
mentioning
confidence: 99%